Environmental and territorial modelling for planning and design Environmental and territorial modelling for planning and design - Antonio Leone (Smart City, Urban Planning for a Sustainable Future, 2018)
[English]: Between 5th and 8th September 2018 the tenth edition of the INPUT conference took place in Viterbo, guests of the beautiful setting of the University of Tuscia and its DAFNE Department. INPUT is managed by an informal group of Italian academic researchers working in many fields related to the exploitation of informatics in planning.This Tenth Edition pursed multiple objectives with a holistic, boundary-less character, to face the complexity of today socio-ecological systems following a systemic approach aimed to problem solving. In particular, the Conference will aim to present the state of art of modeling approaches employed in urban and territorial planning in national and international contexts. Moreover, the conference has hosted a Geodesign workshop, by Carl Steinitz (Harvard Graduate School of Design) and Hrishi Ballal (on skype), Tess Canfield, Michele Campagna. Finally, on the last day of the conference, took place the QGIS hackfest, in which over 20 free software developers from all over Italy discussed the latest news and updates from the QGIS network. The acronym INPUT was born as INformatics for Urban and Regional Planning. In the transition to graphics, unintentionally, the first term was transformed into "Innovation", with a fine example of serendipity, in which a small mistake turns into something new and intriguing. The opportunity is taken to propose to the organizers and the scientific committee of the next appointment to formalize this change of the acronym. This 10th edition was focused on Environmental and Territorial Modeling for planning and design. It has been considered a fundamental theme, especially in relation to the issue of environmental sustainability, which requires a rigorous and in-depth analysis of processes, a theme which can be satisfied by the territorial information systems and, above all, by modeling simulation of processes. In this topic, models are useful with the managerial approach, to highlight the many aspects of complex city and landscape systems. In consequence, their use must be deeply critical, not for rigid forecasts, but as an aid to the management decisions of complex systems.[Italiano]:Dal 5 all'8 settembre 2018 l'Università della Tuscia e il Dipartimento di Scienze Agrarie e Forestali - DAFNE hanno ospitato la decima edizione del Congresso Internazionale INPUT. INPUT è un gruppo informale di ricercatori accademici italiani che operano in molti settori connessi all'uso dell'informatica nella pianificazione.Questa decima edizione del Congresso ha perseguito obiettivi multipli con un carattere olistico, senza confini, per affrontare la complessità degli attuali sistemi socio-ecologici seguendo un approccio sistemico finalizzato alla risoluzione dei problemi. In particolare, la conferenza è stata orientata a presentare lo stato dell'arte degli approcci di modellazione impiegati nella pianificazione urbana e territoriale in contesti nazionali e internazionali.Inoltre, la conferenza ha ospitato un seminario di Geodesign, di Carl Steinitz (Harvard Graduate School of Design) e Hrishi Ballal (via skype), Tess Canfield e Michele Campagna. Infine, l'ultimo giorno della conferenza, si è svolto l'hackfest di QGIS, in cui oltre 20 sviluppatori di software open source provenienti da tutta Italia hanno discusso le ultime novità e gli aggiornamenti dalla rete QGIS.L'acronimo "INPUT" è nato come "INformatics per Urban and Regional Planning". Nella transizione alla grafica, involontariamente, il primo termine è stato trasformato in "Innovazione", con un bell'esempio di serendipità, in cui un piccolo errore si trasforma in qualcosa di nuovo e intrigante.